ANALISIS PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERBANKAN YANG TERDAFTAR DI LQ-45 PERIODE 2015 – 2020 - Mitha Herlita; Nafisah Nurulrahmatia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The purpose of this study was to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER) and Debt Ratio (DR) on stock prices. This research was conducted at a banking company registered in LQ-45. This research uses associative research. The population in this study were all banking companies listed in LQ-45 based on the research period as many as 7 companies and the sample used was 5 companies with the sampling technique used was purposive sampling. The analysis technique used in this study is the classical assumption test and hypothesis testing. Based on the analysis conducted, this study shows that Return On Asset (ROA), Debt to Equity Ratio (DER) and Debt Ratio (DR) have no significant effect on stock prices partially but Return On Asset (ROA), Debt to Equity Ratio (DER) and Debt Ratio (DR) have a significant effect on stock prices simultaneously.